The Analysis of Internet Service Provider (ISP) Service Quality to Maintain Customer Loyalty in The B2B Market - Andhika Mayasari; Fatma Ayu Nuning Farida Afiatna; Sumarsono Sumarsono (OPSI, 2023)
The use of an internet network in an organization cannot be divorced from the numerous types of challenges that occur inside it, particularly those connected to network service quality., In addition, the high demand for service users has become a severe issue where people believe that the network needs to be optimally utilized. This research examined the connection between ISP service quality and B2B customer loyalty to business Internet services. This work employs Structural Equation Modeling with Partial Least Square methodology for SEM data analysis (PLS-SEM). The research revealed a favourable and statistically significant correlation between BP trust and BP loyalty. Because BP believes in the quality and service of ISP providers, they are typically loyal to BP. In addition, NQ and SP have a sizeable direct association with client loyalty. Moreover, this research showed that QSTS had a good and substantial effect on BP's level of trust. Meanwhile, CSTS, NQ, and SP have a favourable and significant impact on BP value.